Nigeria’s Output Gap: A Tool to Inform Economic Policy - Femi Michael Nejo; Abidemi Olufemi Olusegun Falade (Penerbit Hellow Pustaka, 2025)
A vibrant economy is achieved when actual output and potential output grow at an equal proportional, resulting in a zero output gap. In Nigeria of today, actual output may sometime be below its potential capacity or above it, leading to under-utilisation or over utilisation of resources. Therefore, this study examined the growth pattern of actual output and potential output in Nigeria from 2006-2025. The study used secondary data which were collected from the International Monetary Fund, IMF (2025). Thereafter, the study employed Augmented Dickey Fuller (ADF) and Phillip Peron (PP) unit root tests, and Johansen Co-integration for pre-test; while, a ten-year Moving Average (MA) was used to achieve the stated objectives. The ADF and PP unit root test showed the stationary level of the variables at level and at first level difference, the Johansen co-integration established two co-integration relationships at 5% level of significance. The MA technique showed that from 2006-2009, Nigeria’s actual output and potential output were closed aligned, with the country operating near full capacity in 2006 and 2009 respectively. Therefore, implies a zero output gap. From 2011- 2020, actual output was below the potential output; therefore, indicates a negative out-gap. Also, there was high tendency that Nigeria’s actual output gap exceeded potential output gap from 2021-2025. This implies a positive output gap. The study therefore, concluded that the country operated efficiently in 2006-2009, experienced idle capacity from 2011 to 2020, while that of 2021-2025 was over-utilisation of resources. Therefore, recommended that Nigeria government should reduce her excessive borrowing of external or domestic source, in order not to pluck the economy to further overheating. Also, government should invest more on physical and human capital so that the present demand for more workers would not be tentative in nature.